Bangladesh, national culture, and heritage : an introductory reader - Ahmed, A. F. Salahuddin, 1924-; Chowdhury, Bazlul Mobin (Independent University : Distributor, Pathak Shamabesh, 2004)
Contributed articles on history and civilization of Bangladesh in 19th and 20th century.